Qatar : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Swift and decisive policy response to the Covid-19 pandemic has helped to mitigate the health and economic impact of the crisis. Fast vaccination rollout has also strengthened the economy's resilience to new pandemic waves, paving the way for a speedy recovery. As the economy rebounds, a gradual exit from pandemic support measures is underway.